Evaluation of pulmonary hypertension with exercise right heart catheterization in an adult patient with cor triatriatum sinister - NİZAM, AHMET CEM; MUTLU, BÜLENT (My University, 2023)
Cor triatriatum sinister (CTS) is a rare adult congenital heart disease. The usual presentation may vary according to the size of the hole in the membrane in the left atrium and the pressure gradient. In addition to acute clinical presentations including acute pulmonary edema and sudden cardiac death, patients may present with chronic findings such as right heart failure due to pulmonary hypertension. The development of pulmonary hypertension is an important indicator of mortality. In cases where non-invasive methods are not sufficient for the diagnosis of pulmonary hypertension, exercise right heart catheterization may also be used. We present a patient with CTS, in whom the final decision was made with the help of an exercise right heart catheterization.

Cor triatriatum sinister erişkinlerde nadir görülen doğuştan kalp hastalığıdır. Hastaların genel klinikleri sol atriyumdaki zardaki deliğin boyutuna ve basınç gradiyentine göre değişiklik göstermektedir. Hastalar akut pulmoner ödem ve ani kardiyak ölüm gibi akut klinik tabloların yanı sıra pulmoner hipertansiyona bağlı sağ kalp yetmezliği gibi kronik bulgularla başvurabilirler. Pulmoner hipertansiyon gelişimi mortalite için önemli bir göstergedir. Pulmoner hipertansiyon tanısında girişimsel olmayan yöntemlerin yeterli olmadığı durumlarda egzersiz sağ kalp kateterizasyonu da kullanılabilir. Egzersiz sağ kalp kateterizasyonu ile pulmoner hipertansiyon tanısı konulan kor triatriatum sinister bir hastayı sunuyoruz.
Kor triatriatum sinisterli erişkin bir hastada egzersiz sağ kalp kateterizasyonu ile pulmoner hipertansiyonun değerlendirilmesi
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; Konjenital kalp malformasyonu; kor triatriatum; ekokardiyografi; egzersiz sağ kalp kateterizasyonu; pulmoner hipertansiyon